A comparative morphological and morphometric study of the Musculi bulbi oculi and Apparatus lacrimalis in the ostrich (Struthio camelus) and emu (Dromaius novaehallandiae) - Groenewald, Hermanus B. (University of Pretoria, 2018)
Dissertation (MSc)--University of Pretoria, 2017.